A Review of the Academic Historical Work on the May-June 1945 Events in Algeria: A Comparative Study of Algerian and Foreign Writings - Guebaili , Abdelhafid (The Algerian Historical Journal, 2026)
This study aims to provide a comprehensive review of the academic literature on the events of May 1945 in Algeria, focusing on a comparison between Algerian and foreign contributions in quantitative aspects, the terminology used to describe the events, the studied temporal and spatial frameworks, and the research approaches employed. While previous studies have addressed various dimensions of these events, the current literature lacks comprehensive reviews that highlight gaps and research trends, both methodologically and epistemologically. Therefore, the study seeks, through a methodology that combines data collection and analysis, to explore prevailing patterns and identify areas that require further research, along with providing recommendations to enhance academic understanding of this topic and contribute to its development.